Efficacy and safety of traditional Chinese medicine injection with mecobalamin in treating diabetic peripheral neuropathy: A protocol for systematic review and meta-analysis. Issue 1 (8th January 2021) - Mai, Weihua; Wei, Aisheng; Lin, Xiaoxuan; Wang, Funeng; Ye, Jianhong; Chen, Ping
Abstract: Background: Diabetic peripheral neuropathy is a common complication of diabetes and the main cause of disability. At present, there is no specific therapeutic regimen. Mecobalamin is often used as a neurotrophic drug, and its long-term effects are not satisfactory when used alone. Clinical practice indicates that traditional Chinese medicine injection with mecobalamin has a therapeutic advantage in treating diabetic peripheral neuropathy while it lacks evidence-based medicine. In this scheme, the efficacy and safety of traditional Chinese medicine injection with mecobalamin in treating diabetic peripheral neuropathy has been studied. Methods: Computers were used to search the English database (PubMed, the Cochrane Library, Embase, Web of Science), and Chinese database (CNKI, Wanfang, CBMDISC, VIP). Besides, manual searching was conducted to search for Baidu Scholar, CHICTR, Google Scholar. During the establishment of the database to November 2020, a randomized controlled trial on traditional Chinese medicine injection with mecobalamin in treating diabetic peripheral neuropathy was conducted. There were 2 researchers independently conducting data extraction and quality evaluation of literature on the included studies, RevMan5.3 was performed for meta-analysis on the included literature. Results: In this study, the efficacy and safety of traditional Chinese medicine injection with mecobalamin in treating diabetic peripheral neuropathy was evaluated by the total effective rate, motor nerve conduction velocity, sensory nerve conduction velocity, adverse reactions, and glucose metabolism level. Conclusion: This study can provide an evidence-based basis on the clinical applications of traditional Chinese medicine injection with mecobalamin in the treatment of diabetic peripheral neuropathy. Ethics and dissemination: The study does not involve patient privacy or rights and does not require approval from an ethics committee. The results may be published in peer-reviewed journals or disseminated at relevant conferences. OSF Registration number: DOI 10.17605/OSF.IO/KPW5E.